Fox and McDonald's introduction to fluid mechanics - Mitchell, John W.; Fox, Robert W. (1934-2014)
Summary: "Fox, McDonald & Pritchard provide a balanced approach to fluid mechanics that arms students with a proven problem-solving methodology. Students will learn to adopt an orderly approach to solving problems."--BOOK JACKET.